IMPLEMENTASI AKUNTANSI LINGKUNGAN PADA RSUD GAMBIRAN KEDIRI - Buniarto, Edwin Agus (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2020)
This study aims to build a reporting environment based on models of environmental accounting reporting on RSUD Gambiran Kediri locations to determine the actual cost of the accounting treatment of the environment as a form of attention and concern and responsibility of the hospital against hospital waste management. The results of this study can be concluded that the hospital has the objective to provide comprehensive health services through promotion efforts (increased), prevention (prevention), and curative (treatment). As a form of regulation of the Minister of Health of Republic of. 986 / Menkes/Per/XI/1992 on Requirements for Environmental Health Hospital and the Decision of the Director General of PPM and LPM MOH on Requirements, Instructions, and Procedures for Environmental Health Hospital, the hospital established the Installation Environmental Health (IPL). Installation Environmental Health is a unit of applied non-structural organization in the hospital environment that is functional and technical elements of servant leadership is a hospital in planning, implementing, coordinating and evaluating all activities in the field of environmental health / sanitation of the hospital and had a responsible position at the bottom and responsible to the Deputy Director of the hospital finance. Implementation of environmental accounting in hospitals has not been done. Of property in the form of waste processing machines are grouped in public infrastructure and facilities account and not depreciated since the beginning of the year the asset is operated. In a simple short-term review clearly the cost of environmental management will reduce the contribution the operation of hospitals. Environmental management activities conducted in hospitals have been proven true for the internal and external hospital, because of the dangers that may arise from the waste generated can be avoided so the hospital medical staff, patients, visitors and surrounding community can be assured. Construction of environmental accounting in the public sector is very difficult to set up yet because there is a separation allocation of environmental costs in separate accounts.